Impact of oscillometric measurement artefacts in ambulatory blood pressure monitoring on estimates of average blood pressure and of its variability: a pilot study. Issue 1 (20th January 2023) - Bothe, Tomas L.; Bilo, Grzegorz; Parati, Gianfranco; Haberl, Ralph; Pilz, Niklas; Patzak, Andreas
Abstract : Objective: Ambulatory blood pressure monitoring (ABPM) plays an important role in the diagnosis of hypertension. However, methodological factors and the measurement conditions affect the results and may lead to incorrect classification of the patient. We performed a pilot study to evaluate the impact of oscillometric measurement artefacts on ABPM-derived variables. Methods: Four classes of artefacts have been detected: motor activity artefacts, cuff errors, cardiovascular arousals, and arrhythmias. The data consisted of uncorrected measurements (all data), corrected measurements (all artefact free data), and artefact affected data. Results: A total of 30 individuals (9 female/21 male), aged between 36 and 86 years, mean: 65.5 (standard deviation: 9.5) were included in the study. The average blood pressure (BP) was higher in artefacts-affected measurements compared the artefact-free measurements both for systolic (4.6 mmHg) and diastolic (1.3 mmHg) measurements. Further, artefact-affected systolic BP (SBP) was 6.4 mmHg higher than artefact-free measurements during daytime. Nocturnal measurements showed no artefact-depended differences. Individual comparisons yielded that 23% of the participants crossed the threshold for BP classification for either 24-h, daytime or nocturnal hypertension when comparing uncorrected and artefact-free measurements. Dipping classification changed within 24% of participants. BP variability was 21 and 12% higher for SPB and DBP, respectively, during daytime. These differences were even higher (27% for SBP and 21% for DPB) during night-time. Conclusion: The study reveals that measurement artefacts are frequently present during cuff-based ABPM and do relevantly affect measurement outcome. Exclusion of measurement artefacts is a promising approach to improving cuff-based ABPM accuracy.